Biosorption of Zn(II) from aquoues solution by jatropha curcas press cake - Zainal Abidin, Zurina; Mohd Salleh, Mohamad Amran; Harun, Mohd Yusof; Abu Bakar, N. (National Institute of Science Communication and Information Resources - Council of Scientific and Industrial Research, 2014)
Biosorption of Zn (II) from aqueous solution using Jatropha curcas press cake was comparatively investigated over a range of variables (contact time, pH, and initial metal concentration) by batch adsorption experiments. Highest Zn (II) removal (~40 mg/L) was attained using 0.5g adsorbent for 100 minutes with initial Zn (II) concentration of 50 mg/L and pH 4. The adsorption data was best fitted with Langmuir isotherm (R2 = 0.99) and follows second order kinetic rate equation (R2 > 0.99). FTIR analysis revealed the availability of phenol, alcohol and carboxyl functional groups in Jatropha curcas press cake for the biosorption. XRD results confirmed the presence of Zn (II) in the press cake after adsorption process. These findings concluded that Jatropha curcas press cake is a suitable biosorbent for removing Zn (II) in heavy metal polluted wastewater.